2007
DOI: 10.1177/112067210701700411
|View full text |Cite
|
Sign up to set email alerts
|

Role of Central Corneal Thickness on Baseline Parameters and Progression of Visual Fields in Open Angle Glaucoma

Abstract: Patients with thinner corneas initially present with a greater visual field defect, indicating that thin corneas may contribute to advanced glaucomatous damage at the time of diagnosis. However, CCT does not seem to be a significant risk factor for progression of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
0
12
0
2
Order By: Relevance
“…After the landmark investigations by the Ocular Hypertension Treatment Study Group, reporting that a thin cornea was a significant risk factor for the progression from ocular hypertension to primary open-angle glaucoma [1], it was logical to assume that such a finding may be due to an association between a thin cornea as "anterior roof" of the ocular globe and the lamina cribrosa as "posterior roof" of the globe. The observations made in the Ocular Hypertension Treatment Study were supported by other hospital-based and population-based studies such as the European Glaucoma Prevention Study and the Early Manifest Glaucoma Trial, in which subjects with a thin cornea had a higher risk for development or progression of glaucoma, while some other studies did not agree with an association between a thin cornea and increased glaucoma susceptibility [15][16][17][18][19][20][21][22][23][24][25][26][27][28]. To cite an example, in a follow-up study on patients with established glaucoma by Chauhan and colleagues, central corneal thickness was not a useful index in the risk assessment of visual field and optic disc progression [27].…”
Section: Discussionmentioning
confidence: 98%
“…After the landmark investigations by the Ocular Hypertension Treatment Study Group, reporting that a thin cornea was a significant risk factor for the progression from ocular hypertension to primary open-angle glaucoma [1], it was logical to assume that such a finding may be due to an association between a thin cornea as "anterior roof" of the ocular globe and the lamina cribrosa as "posterior roof" of the globe. The observations made in the Ocular Hypertension Treatment Study were supported by other hospital-based and population-based studies such as the European Glaucoma Prevention Study and the Early Manifest Glaucoma Trial, in which subjects with a thin cornea had a higher risk for development or progression of glaucoma, while some other studies did not agree with an association between a thin cornea and increased glaucoma susceptibility [15][16][17][18][19][20][21][22][23][24][25][26][27][28]. To cite an example, in a follow-up study on patients with established glaucoma by Chauhan and colleagues, central corneal thickness was not a useful index in the risk assessment of visual field and optic disc progression [27].…”
Section: Discussionmentioning
confidence: 98%
“…The most important reason why studies did not meet the high quality criteria was their retrospective design (38.3% of studies reviewed). 10,[30][31][32]34,36,38,39,43,48,53,58,59,61,64,[66][67][68][69] In retrospective studies (historical cohorts), the information contained in the registries may be missing (incomplete) or of poor quality (information bias). 16 In contrast, in retrospective studies, progression and exposure to PFs occurs before the actual start of the research.…”
Section: Discussionmentioning
confidence: 99%
“…Its role in disease progression is less well understood. Recent studies [29][30][31] have suggested that CCT may not be related to glaucoma progression. CCT may have a stronger significance in diagnosis than on progression after diagnosis [29,31].…”
Section: Central Corneal Thicknessmentioning
confidence: 97%